The lives of women: a new history of inquisitional Spain - Vollendorf, Lisa (Vanderbilt Univ. Press, 2005)
Defining gender: the Inquisition -- 'I am a man and a woman': Eleno/a de Cäspedes faces the Inquisition -- Bernarda Manuel: defending femininity to the Holy Office -- Imagining gender: women and their readers -- Women in fiction: Maræa de Zayas and Mariana de Carvajal -- Women onstage: Angela de Azevedo, Maræa de Zayas, and Ana Caro -- Women's worlds: convent culture -- Nuns as writers: the cloister and beyond -- Nuns as mothers: biology and spirituality -- Women's networks: leadership and community -- Single women: the price of independence -- Toward a history of women's education -- Conclusion.